Trade, Global Value Chains and Development: What Role for National Development Banks? - Petra Dünhaupt; Hansjörg Herr (Vierteljahrshefte zur Wirtschaftsforschung, 2020)
In this article we discuss the need for industrial policy and role of development banks for economic development. The catching-up of countries in the Global South to productivity levels and living standards of the Global North is the exception. There are two main economic explanations for this observation. First, developing countries are pushed to low-tech and labor-intensive productions and tasks in global value chains. This offers the advantage of easier industrialisation, but it does not automatically lead to productivity levels comparable with the Global North. Foreign direct investments only partially help to overcome this problem. Second, low trust in national currencies in the Global South leads to distorted financial markets which do not provide sufficient credit for investment. National development banks play a key role in facilitating the economic catching-up of the Global South as part of needed industrial policies. They can alleviate distortions in the financial system and at the same time support the transformation of the economy towards higher productivity and ecological transformation. We explain development bank policies by using the KfW as an example of an effective industrial policy. – – In diesem Artikel diskutieren wir die Notwendigkeit von Industriepolitik und die Rolle der Entwicklungsbanken für wirtschaftliche Entwicklung. Der Aufholprozess der Länder des globalen Südens auf das Produktivitätsniveau und den Lebensstandard des globalen Nordens ist die Ausnahme. Dafür gibt es im Wesentlichen zwei ökonomische Erklärungen. Erstens werden die Entwicklungsländer zu Low-Tech- und arbeitsintensiven Produktionen und Aufgaben in globalen Wertschöpfungsketten gedrängt. Dies bietet den Vorteil einer leichteren Industrialisierung, führt aber nicht automatisch zu Produktivitätsniveaus, die mit denen des globalen Nordens vergleichbar sind. Ausländische Direktinvestitionen tragen nur teilweise zur Überwindung dieses Problems bei. Zweitens führt das geringe Vertrauen in die nationalen Währungen im globalen Süden zu einer Störung der Finanzmärkte, die keine ausreichenden Kredite für Investitionen bereitstellen. Nationale Entwicklungsbanken spielen eine Schlüsselrolle bei der Erleichterung des wirtschaftlichen Aufholprozesses des globalen Südens als Teil der notwendigen Industriepolitik. Sie können Verzerrungen im Finanzsystem mildern und gleichzeitig die Transformation der Wirtschaft hin zu höherer Produktivität und ökologischer Transformation unterstützen. Am Beispiel der KfW erläutern wir die Entwicklungsbankpolitik als Beispiel für eine effektive Industriepolitik.
Keywords: E44; F10; F63; 330; Trade theory; economic development; global value chains; industrial policy; financial systems; dollarisation; development banks